A Rising Tide? The Local Incidence of the Second Wave of Globalization - Rowena Gray; Greg C. Wright (Center for Economic Studies and ifo Institute (CESifo), 2022)
We estimate the short- and long-run local labor market impacts of the large increase in U.S. imports and exports that occurred over the 1970s. We exploit the sequential opening of overseas shipping container ports over the period, which generated discontinuous changes in U.S. trade ows. We find that the impacts of the export shock on employment, income, and home and rental prices were large, but short-lived, suggesting that U.S. local labor markets equilibrated quickly. The import effects were also large and mostly short-lived, but we find strong persistence in the impact on home and rental prices. We exploit differences in housing supply elasticities across markets to show that this is due to the fact that the housing stock is durable and so does not easily contract, a result with important welfare implications. Overall, we estimate that the net impact of the shock was to raise manufacturing sector employment by 250,000 workers over the decade of the 1970s.
Keywords: F14; F16; F66; J21; R31; 330; containerization; international trade; globalization; housing durability